How the land system with Chinese characteristics affects China's economic growth: An analysis based on a multisector dynamic general equilibrium framework - Kai Liu (China Political Economy (CPE), 2020)
Purpose What is the relation between the land system with Chinese characteristics and the country's high-speed economic growth in the past decades? There is a lack of rigorous academic research based on the general equilibrium theory of macroeconomics on this issue. Design/methodology/approach By building a multisector dynamic general equilibrium framework with land system, this paper explores how the land supply mode with Chinese characteristics affects China's economic growth as well as its transmission mechanism. Findings This paper confirms the importance of land system with Chinese characteristics in explaining the mystery of China's high-speed economic growth. Counterfactual analysis shows that if China adopts a land system similar to that of other developing countries, GDP will drop 36% from the current level under the baseline model. Originality/value As the industrial sector shrinks relatively and the output elasticity of infrastructure decreases, this inhibitory effect will become more apparent. China should improve its land supply mode, especially expand the supply of commercial and residential land and reduce the cost of land in the service sector. This can promote better economic development in the future and thus improve household welfare and the structure of aggregate demand, replace "land-based public finance" and thus inhibit the "high leverage" risks of local governments.
Keywords: H27; H41; O41; O43; P26; 330; Economic growth; Infrastructure; Land system; Land-based public finance